Controllable Magnetic Proximity Effect and Charge Transfer in 2D Semiconductor and Double‐Layered Perovskite Manganese Oxide van der Waals Heterostructure. Issue 50 (28th October 2020) - Zhang, Yan; Shinokita, Keisuke; Watanabe, Kenji; Taniguchi, Takashi; Goto, Masato; Kan, Daisuke; Shimakawa, Yuichi; Moritomo, Yutaka; Nishihara, Taishi; Miyauchi, Yuhei; Matsuda, Kazunari
Abstract: Optically generated excitonic states (excitons and trions) in transition metal dichalcogenides are highly sensitive to the electronic and magnetic properties of the materials underneath. Modulation and control of the excitonic states in a novel van der Waals (vdW) heterostructure of monolayer MoSe2 on double‐layered perovskite Mn oxide ((La0.8 Nd0.2 )1.2 Sr1.8 Mn2 O7 ) is demonstrated, wherein the Mn oxide transforms from a paramagnetic insulator to a ferromagnetic metal. A discontinuous change in the exciton photoluminescence intensity via dielectric screening is observed. Further, a relatively high trion intensity is discovered due to the charge transfer from metallic Mn oxide under the Curie temperature. Moreover, the vdW heterostructures with an ultrathin h ‐BN spacer layer demonstrate enhanced valley splitting and polarization of excitonic states due to the proximity effect of the ferromagnetic spins of Mn oxide. The controllable h ‐BN thickness in vdW heterostructures reveals a several‐nanometer‐long scale of charge transfer as well as a magnetic proximity effect. The vdW heterostructure allows modulation and control of the excitonic states via dielectric screening, charge carriers, and magnetic spins. Abstract : A novel van der Waals heterostructure consisting of monolayer MoSe2, Mn oxide, and a buffer layer ( h ‐BN) demonstrates magnetic proximity and charge transfer effect for the excitonic states due to phase transition of Mn oxide from ferromagnetic metal to paramagnetic insulator. The controllable thickness of h ‐BN reveals a characteristic length scale of several nanometers in magnetic proximity and charge transfer.